Helicobacter pylori-induced cell death is counteracted by NF-κB-mediated transcription of DARPP-32. Issue 5 (2nd September 2016) - Zhu, Shoumin; Soutto, Mohammed; Chen, Zheng; Peng, DunFa; Romero-Gallo, Judith; Krishna, Uma S; Belkhiri, Abbes; Washington, M Kay; Peek, Richard; El-Rifai, Wael
Abstract : Objective: DARPP-32 is a frequently amplified and overexpressed gene that promotes several oncogenic functions in gastric cancer. Herein, we investigated the relationship between Helicobacter pylori infection, proinflammatory NF-κB activation and regulation of DARPP-32. Design: The study used in vivo and in vitro experiments. Luciferase reporter, quantitative real-time PCR, immunoblot, chromatin immunoprecipitation (ChIP), cell viability, H. pylori infection, tissue microarrays and immunohistochemical assays were used. Results: Our results indicated that H. pylori infection increased the DARPP-32 mRNA and protein levels in gastric cancer cell lines and gastric mucosa of mice. H. pylori infection increased the activity of NF-κB reporter and p-NF-κB (S536) protein level in vitro and in vivo . To investigate the transcriptional regulation of DARPP-32, we cloned a 3019 bp of the DARPP-32 promoter into the luciferase reporter (pGL3-Luc). Both H. pylori infection and tumour necrosis factor-α treatment induced DARPP-32 reporter activity (p<0.01). Using deletion constructs of DARPP-32 promoter and ChIP assay, we demonstrated that the sequence −996 to −1008 bp containing putative NF-κB-binding sites is the most active region. The induction of DARPP-32 expression by H. pylori infection counteracted H. pylori -induced cell death through activation of serine/threonine-specific protein kinase (AKT), as determined by ATP-Glo and clonogenic survival assays. Immunohistochemistry analysis demonstrated a significant positive correlation between NF-κB and DARPP-32 expression levels in gastric cancer tissues (r 2 =0.43, p<0.01). Conclusions: Given the high frequency of DARPP-32 overexpression and its prosurvival oncogenic functions, the induction of DARPP-32 expression following H. pylori infection and activation of NF-κB provides a link between infection, inflammation and gastric tumourigenesis.